Smart Jacket / Nur Atiqah Shariffuddin … [et al.] - SHARIFFUDDIN, NUR ATIQAH; MOHAMAD RUSOP, NUR AUNI; MOHAMAD RUSOP, NUR INANI; MD KHAIRI, NURUL FARHANA (2018)
Jacket is mostly used during travelling. The idea of developing the 'Smart Jacket' is from our observation throughout the market survey and observation, there are lots of types of jacket in the market but the one that we produced is a travel friendly and similar like others but has improved in terms of technologies to serve the demand. This product is an innovation product to the commercialized travelling jacket that available in the market. In addition, this smart jacket with the elegant design and features which can give the person who wear it feeling comfort and easier when travelling, reducing the stress mode and suitable to wear in casual day or night (one jacket for all).It is easy to find a jacket in the market, but a jacket only is not enough as multifunction jacket is more practical for users today to ease them.